CEO Compensation and Concurrent Executive Employment of Outside Directors: A Panel Data Analysis of S&P 1500 firms - Young-Chul Kim; Su Jin Song (KDI Journal of Economic Policy, 2016)
In many advanced countries, most outside directors are executives, active or retired, at other firms; in other words, executives from other companies make executive compensation decisions. This situation may hinder the board of directors (BOD) in their efforts to optimize executive compensation levels objectively. Using a panel data analysis of the S&P 1500 companies, we provide supplemental evidence of whether, and to what extent, the concurrent executive employment of outside directors distorts the executive pay decisions at a given company. An unbiased fixed-effect estimation confirms that a 1.00 increase in CEO pay at outside directors' primary companies results in an approximate increase of 0.22 in CEO pay at the given company. From a policy perspective, this added agency problem — caused by the BOD and not by management — is noted as difficult to control; although a firm may establish board independence, the inherent concurrent employment of directors on a board continues to exist.
Keywords: M12; G34; G38; 330; CEO Compensation; DirectorAgency Problem; H825Outside Directors; Board of Directors; Corporate Governance